Unusually-high growth rate (∼2.8 μm/s) of germania nanowires and its hierarchical structures by an in-situ continuous precursor supply - Wu, Shaoteng (2021)
Low-dimensional nanostructured semiconductors are becoming the promising materials for the further high-performance nanophotonics, nanoelectronics, and quantum devices. To enable these applications, it requires an efficient methodology to control the dimension of the materials during synthesis processes and to achieve mass production of these materials with reproducibility, perfect crystallinity, and low cost. In this study, an ultra-fast, facile synthesis strategy is presented for reproducible monocrystalline hexagonal germania (GeO2) nanowires (NWs) and hierarchical structures. These GeO2 nanostructures were grown in one step by annealing of the Ni- film-covered GeSn epilayers in a rapid thermal annealing system without any gaseous or liquid Ge sources. It was found that after short annealing for 60 s at 675 °C, the longest GeO2 NWs were more than 170 µm, indicating that the growth rate is several magnitude orders higher than that of the common chemical vapor deposition (CVD) methods. The mechanism of the growth was studied by changing the growth temperature, catalyst type, and surface oxidation. The results indicate that this record-fast growth (>2.8 um/s) of NW is due to the continuously generated in-situ GeO vapors from the Ni-catalyst decomposition of supersaturated GeSn epilayer. This work presents a high-efficiency, low-cost, and wafer-scale method to synthesis high-density GeO2 NW and its hierarchical structures which have the potential applications for optoelectronic communication/detection, superhydrophobic surfaces, photocatalyst, and sensing.